2021
DOI: 10.3354/ame01973
|View full text |Cite
|
Sign up to set email alerts
|

Human impact on symbioses between aquatic organisms and microbes

Abstract: Aquatic organisms rely on microbial symbionts for coping with various challenges they encounter during stress and for defending themselves against predators, pathogens and parasites. Microbial symbionts are also often indispensable for the host's development or life cycle completion. Many aquatic ecosystems are currently under pressure due to diverse human activities that have a profound impact on ecosystem functioning. These human activities are also ex pected to alter interactions between aquatic hosts and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 278 publications
(180 reference statements)
0
14
0
Order By: Relevance
“…In Hydra , an increased tolerance to copper has been associated with the presence of microalgal symbionts (Karntanut & Pascoe, 2005), while in metal‐rich hydrothermal vent environments, symbiotic bacteria on mussels ( Bathymodiolus ; Hardivillier et al ., 2004) protect their host by transforming absorbed metal ions into metal particles. Additionally, microbial symbionts of aquatic invertebrates frequently provide their hosts with crucial micronutrients (Stock et al ., 2021). As an example, the settling of poriferan, cnidarian and mollusc larvae requires bacteria.…”
Section: Certainties and Uncertainties In Assessing Aquatic Ecotoxico...mentioning
confidence: 99%
“…In Hydra , an increased tolerance to copper has been associated with the presence of microalgal symbionts (Karntanut & Pascoe, 2005), while in metal‐rich hydrothermal vent environments, symbiotic bacteria on mussels ( Bathymodiolus ; Hardivillier et al ., 2004) protect their host by transforming absorbed metal ions into metal particles. Additionally, microbial symbionts of aquatic invertebrates frequently provide their hosts with crucial micronutrients (Stock et al ., 2021). As an example, the settling of poriferan, cnidarian and mollusc larvae requires bacteria.…”
Section: Certainties and Uncertainties In Assessing Aquatic Ecotoxico...mentioning
confidence: 99%
“…There are precedents with mosquito-borne diseases, such as malaria, dengue and chikungunya, where the release of microbiome-altered vectors reduced disease prevalence, both at a local and at a regional scale [3,9,10]. It is hypothesized that microbiomes might affect the outcome of parasitic flatworm infections in snails by competing for resources, producing antimicrobials or stimulating the host's immune response [11][12][13][14].…”
Section: Main Textmentioning
confidence: 99%
“…Although such controlled laboratory experiments will undoubtedly provide vital insights into the tripartite interaction between snails, bacteria and parasitic flatworms, extrapolation of patterns and protocols to field settings might prove complicated [5]. However, correlative field-based studies could fill these caveats and, likewise, transplant experiments could help discern correlation from causation in a controlled setting [14]. Correlative studies could help in identifying bacterial strains involved in snail resistance.…”
mentioning
confidence: 99%
“…Eckert et al 183 reported that zooplankton living in the same environment share similar microbes and have a similar richness, thus suggesting the influence of the environment on the microbiome of the zooplankton. An increase in water temperature can affect the host microbial community, either directly or indirectly by influencing the host physiology 186–188 . At temperatures above 15°C, the ability of V. cholerae to attach to chitinous surfaces of zooplankton is altered by increasing water temperature as a result of increased expression of the MSHA pilus and colonization factor GbpA 95 .…”
Section: Potential Effects Of Abiotic Environmental Conditions On Pat...mentioning
confidence: 99%
“…An increase in water temperature can affect the host microbial community, either directly or indirectly by influencing the host physiology. 186 , 187 , 188 At temperatures above 15°C, the ability of V. cholerae to attach to chitinous surfaces of zooplankton is altered by increasing water temperature as a result of increased expression of the MSHA pilus and colonization factor GbpA. 95 Water temperature does not seem to be the sole factor controlling this association, however, as planktonic V. cholerae are more frequent than zooplankton‐associated forms at temperatures above 15°C in the Chesapeake Bay.…”
Section: Potential Effects Of Abiotic Environmental Conditions On Pat...mentioning
confidence: 99%